PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN VEGETATIF TANAMAN MENTIMUN (Cucumis sativus L.) - Arisandi, Nirmela; Mulyati, Mulyati; Novi, Novi (Pendidikan Biologi, 2013)
ABSTRAK Cucumber is an annual plant that is pervasive belonging to Cucurbitaceae family are widely used as food , cosmetic and drug industry - abatan . Low productivity and quality of cucumber caused less intensive farming techniques , one of which depends on fertilization and treatments performed . The initial step was  to  produce  healthy  seedlings  with  optimal  growth  is  to  find  a  suitable growing media for planting cucumbers . To find the appropriate planting medium with the plant roots need to combine the organic material and adapted to the type of plant . In connection with that have done research that aims to find a suitable planting medium for the growth of cucumber plants . The research was conducted in the village Kajai , Talamau District , West Pasaman . This type of research is experimental , with a completely randomized design ( CRD ) consisting of 5 treatments and 5 replications . The treatments were A ( soil as a control ) , B ( garden soil + sand ) , C ( garden soil + manure ) , D ( cow manure + sand ) , E ( garden soil + sand + cow manure ) . The data were analyzed with analysis of variance and followed by LSD test at 5% level . The results showed that the use of a combination  of  growing media  can  increase  the percentage  of  live  seeds  , number of leaves and plant height . The best growth results found on the treatment E.